Diagnostic performance of machine learning models based on dual-phase 99mTc-MIBI SPECT/CT semiquantitative parameters for differentiating benign and malignant pulmonary nodules - Kun Zhang; Xin Zhou; Yuhang Zhang; Gang Jin; Ping Li; Yuzhuo Xing (PLoS ONE, 2026)
Purpose To evaluate the diagnostic value of machine learning models based on dual-phase 99 mTc-MIBI SPECT/CT semiquantitative parameters for differentiating benign and malignant pulmonary nodules. Methods This retrospective study included 132 patients with pulmonary nodules, including 30 benign and 102 malignant lesions. All patients underwent dual-phase 99 mTc-MIBI SPECT/CT at approximately 20 minutes and 2 hours after tracer injection. Semiquantitative parameters, including early and delayed tumor-to-normal ratios (T/N) and retention indices (RI), were calculated. Clinical variables and imaging parameters were analyzed using univariable and multivariable logistic regression, and selected variables were further used to develop machine learning models. Results Malignant nodules showed significantly higher early-phase uptake and lower retention index values than benign nodules. Multivariable analysis identified elevated CEA and RImax as independent predictors of malignancy. Machine learning models built on these simple semiquantitative parameters showed promising diagnostic performance, with an AUC of 0.944 (95% CI: 0.883–0.990) for SVM on the training set, 0.805 (95% CI: 0.678–0.912) for Logistic Regression (LR), 0.881 (95% CI: 0.800–0.949) for Artificial Neural Network (ANN), and 0.979 (95% CI: 0.951–0.995) for Random Forest (RF), demonstrating their effectiveness in classifying pulmonary nodules. Conclusion Dual-phase 99 mTc-MIBI SPECT/CT semiquantitative parameters provide useful information for distinguishing benign from malignant pulmonary nodules. A machine learning strategy based on simple and interpretable parameters may offer a practical tool for pulmonary nodule assessment, especially in settings where complex imaging analysis is not feasible.